Effect of Glutamine-Supplemented Extender on Kinematics and Quality of Cryopreserved Epididymal Sperm of Barb Stallions - Aouane, Nedjma; Metref, Ahmed Khireddine; Nabi, Ibrahim; Belala, Redha (The Indian Journal of Animal Reproduction, 2024)
The aim of the present study was to evaluate the effect of glutamine on the motility parameters after thawing of epididymal semen of Barb stallions. Semen samples were collected from 22 testicles of slaughtered Barb stallions by retrograde flushing technique. Semen samples were aliquoted and diluted with the following extenders, (1) base medium (BM) (INRA96®+2.5%glycerol+2% egg yolk); (2) BM+25mM Glutamine (C25); (3) BM+50mM Glutamine (C50); (4) BM+75mM Glutamine (C75) and (5) BM+100mM Glutamine (C100). The assessment of Kinematic parameters was established after thawing by using SPA® spain CASA (Computer Automated Sperm Analyzer); and the plasma membrane functional integrity was analyzed by HOST test. At low concentrations, the presence of glutamine (C25 and C50) improved significantly (p<0.05) the kinematics variables (VSL, VAP, LIN and STR). However, higher concentrations of glutamine (C75 and especially C100) significantly decreased the movement of thawed semen. In conclusion, these observations are showing a beneficial effect of glutamine on sperm kinematics at low concentrations and indicated a toxic effect at high concentrations, although, no differences were observed in terms of HOST integrity.